NEONATAL MORTALITY IN INDIA: EMERGING PARADOXES - K.S. James Ian Aitken S.V. Subramanian (HCPDS Working Paper Series Volume 10 Number 13, 2000)
This paper attempts to bring the major factors that influence neonatal mortality in India. Existing child survival strategies have mainly focused on children above one month. As a result, there has been a disproportionate decline in postneonatal and child mortality compared to neonatal mortality, with the decline being smaller in neonatal mortality. Presently, neonatal mortality constitute over 65 percent of all infant deaths. The proximate determinants to neonatal mortality, as revealed through different conceptual and empirical studies, are reviewed within the Indian context. The importance of demographic factors (birth interval and birth order), nutritional level of mother and factors associated with mother's socio-economic status (infection and health seeking behavior) to neonatal mortality are often emphasized by existing studies. The statistical analysis using the Indian National Family Health Survey substantiated the importance of birth interval and nutritional level for neonatal mortality. The study calls for an urgent need to focus on neonatal mortality for any further reduction in infant mortality with special emphasis on factors that operate at the level of mothers.